Implementation of Milleu Teaching: Improving Receptive and Expressive Language Skills in Early Childhood with Language Delay - Meydina Muharramah Putri Diliyanty; Endah Mastuti (Psikostudia : Jurnal Psikologi, 2024)
This study aims to determine the effectiveness of the implementation of the milieu teaching approach as an intervention to improve receptive and expressive language skills in early childhood experiencing language delays. The research design used a single-case experimental design. The subject of this study was a boy aged 4 years and 11 months who had a delay in language development. Data were collected through various assessments (interviews, observations, and formal psychological tests). The results showed that there were significant changes in expressive and receptive language skills after being given milieu teaching through A-B-A analysis. This means that milieu teaching is effective in improving the language skills of early childhood experiencing language delays. The practical implication is the importance of the role of parents in providing appropriate and consistent stimuli to children, as well as the importance of awareness of the influence of the environment on learning. Penelitian ini bertujuan untuk mengetahui efektivitas implementasi pendekatan milleu teaching sebagai intervensi untuk meningkatkan kemampuan bahasa reseptif dan ekspresif anak usia dini yang mengalami keterlambatan bahasa. Desain penelitian menggunakan desain eksperimen kasus tunggal. Subjek penelitian ini adalah anak laki-laki berusia 4 tahun 11 bulan yang memiliki keterlambatan dalam perkembangan bahasa. Pengumpulan data dilakukan melalui berbagai asesmen (wawancara, observasi, dan tes formal psikologi). Hasil penelitian menunjukkan bahwa terdapat perubahan yang signifikan dalam kemampuan bahasa bahasa ekspresif dan reseptif setelah diberikan milleu teaching melalui analisis A-B-A. Artinya, milleu teaching  efektif dalam meningkatkan kemampuan bahasa anak usia dini yang mengalami keterlambatan bahasa. Implikasi praktisnya adalah pentingnya peran orang tua dalam memberikan stimulus yang sesuai dan konsisten kepada anak, serta pentingnya kesadaran akan pengaruh lingkungan dalam pembelajaran.